Analiza različitih aspekata partnerskih odnosa kod polaznika zaručničkih tečajeva i važnost vjere u njihovu životu - Volenik, Antun; Blažeka Kokorić, Slavica; Laklija, Maja (2021)
U radu su prikazani rezultati istraživanja provedenoga na uzorku od 245 osoba (122 para) koji polaze zaručnički tečaj kao sastavni dio bliže pripreme za sklapanje sakramentalnoga braka u okviru Katoličke crkve. Cilj je istraživanja bio ispitati obilježja partnerskih odnosa zaručnika koji se nalaze u fazi bliže pripreme za brak koji u sebi uključuje sakramentalnu dimenziju. Dodatno, istraživanjem se je željelo provjeriti postoje li razlike u obilježjima partnerskih odnosa ovisno o procjeni važnosti vjere u osobnom životu sudionika istraživanja. Dobiveni rezultati pokazali su da je kod 71% sudionika istraživanja prisutan zajednički život zaručnika prije braka, 11% njih ulazi u brak s trudnoćom, a još 8,3% s već rođenim zajedničkim djetetom. Kod zaručnika koji procjenjuju važnost vjere u osobnom životu višim procjenama, bitno je rjeđe prisutna kohabitacija.
The paper presents the results of a survey conducted on a sample of 244 persons (122 couples) attending a Marriage Preparation Course as an integral part of the immediate preparation for the celebration of the Sacrament of Marriage within the Catholic Church. The aim of the research was to examine the characteristics of engaged couples who are in the phase of immediate preparation for marriage which includes the sacramental dimension. Also, the research tested for differences in the characteristics of such couples depending on an assessment of the importance of faith in their personal life. The results showed that 71% of the participants lived a joint life with their fiancé/fiancée before marriage, 11% of them entered marriage already expecting a child, and another 8.3% with their child already born. Cohabitation is significantly less frequent in the case of engaged couples who exhibited the importance of faith in their personal life to a higher degree. The data obtained in this part of the research showed that as many as 71.0% of research participants consider religion to be important or extremely important in their lives and only 6.5% consider it unimportant or extremely unimportant. The results obtained through ANOVA showed that - between the groups of fiancés who lived together before marriage and those who did not - there is a statistically significant difference which is contingent upon the importance of faith in one's personal life, especially in terms of the differences in attitude between men and women. Based on the data obtained, the article addresses the current state of marriage and family pastoral care in the Republic of Croatia and proposes some adjustments with regard to the premarital life of the majority of couples.
Bibliografske bilješke uz tekst ; bibliografija: str. 109-110.
Sažetak ; Summary.
Keywords: Brak -- Sakrament ženidbe -- Priprema za brak -- Partnerski odnosi; Katolička crkva